Evidence for antimicrobial and anticancer activity of pituitary adenylate cyclase-activating polypeptide (PACAP) from North African catfish (Clarias gariepinus): Its potential use as novel therapeutic agent in fish and humans. Issue 86 (March 2019) - Lugo, Juana Maria; Tafalla, Carolina; Oliva, Ayme; Pons, Tirso; Oliva, Brizaida; Aquilino, Carolina; Morales, Reynold; Estrada, Mario Pablo
Abstract: Pituitary adenylate cyclase-activating polypeptide (PACAP) is a regulatory neuropeptide that belongs to the secretin/glucagon superfamily, of which some members have shown antimicrobial activities. Contrasting to mammals, published studies on the action of PACAP in non-mammalian vertebrate immune system remain scarce. Some of our recent studies added this peptide to the growing list of mediators that allow cross-talk between the nervous, endocrine and immune systems in teleost fish. Regulation of PACAP and expression of its receptor genes has been demonstrated during an immune response mounted against acute bacterial infection in fish, though the direct effect of PACAP against fish pathogenic bacteria has never been addressed. Current work provides evidence of antimicrobial activity of Clarias gariepinus PACAP against a wide spectrum of Gram-negative and Gram-positive bacteria and fungi of interest for human medicine and aquaculture, in which computational prediction studies supported the putative PACAP therapeutic activity. Results also indicated that catfish PACAP not only exhibits inhibitory effects on pathogen growth, but also affects the proliferation of human non-small cell lung cancer cell line H460 in a dose-dependent manner. The observed cytotoxic activity of catfish PACAP against human tumor cells and pathogenic microorganisms, but not healthy fish and mammalian erythrocytes support a potential physiological role of this neuropeptide in selective microbial and cancer cell killing. All together, our findings extend the mechanisms by which PACAP could contribute to immune responses, and open up new avenues for future therapeutic application of this bioactive neuropeptide. Highlights: Evidence for antimicrobial and anticancer activity of a catfish pituitary adenylate cyclase-activating polypeptide (PACAP). Potential use of catfish PACAP as novel therapeutic agent in fish and humans. Computational prediction studies supported the putative catfish PACAP therapeutic activity.